Do chatbots support consumer performance? Investigating the role of E-lifestyle and anthropomorphism in the service industry - Retno Dewanti; Ridho Bramulya Ikhsan (International Journal of Information Management Data Insights)
The growing implementation of chatbots in the service industry reflects continued innovation in this area. However, concerns persist regarding chatbot competence in addressing consumer inquiries, potentially hindering both the interaction experience and consumer performance. This study investigates the factors driving consumer performance in chatbot interactions. Data were collected via an online survey of 336 Indonesian consumers. Partial least squares-structural equation modeling (PLS-SEM) was employed to test the structural model. The findings reveal that e-lifestyle significantly influences both chatbot experience and competence. Anthropomorphism significantly impacts chatbot experience, competence, and the resulting consumer performance. Moreover, both chatbot experience and competence significantly affect consumer performance. Furthermore, chatbot competence significantly shapes the user experience. This study contributes to both theoretical and practical understanding of chatbots within the service industry.